Między Wschodem a Zachodem. Polska Josifa Brodskiego - Tarkowska, Joanna (Acta Polono-Ruthenica, 2006)
The article aims at a discussion of Iosip Brodsky’s literary, artistic as well as personal connections with Poland and Poles. The poet’s admiration for Polish language and especially his fascination with the literature of the Renaissance period (Kochanowski, Sęp-Szarzyński, Rej and others) and modern poetry (Miłosz, Herbert, Szymborska and others) have been one of the main focuses of the article. The author highlights that fact that thanks to the presence of Polish motifs the poetry of Iosip Brodsky, in the times of important events in the history of Poland, had a special appeal for Polish readers. Brodsky’s eminent friends associated with the Solidarity movement, such as Barańczak, Drawicz and Woroszylski, pointed to its intertextual and, at times, documentary character. The article offers also an insight into Brodsky’s friendship with Miłosz, the friendship which greatly contributed to the Russian poet’s fascination with Polish culture.